Evolusi Ideologi: Pengaruh Tan Malaka terhadap Politik Indonesia, 1921-1949 - Setiawan, Aris; Subaryana, Subaryana; Lestari, Siska Nurazizah (Warisan: Journal of History and Cultural Heritage, 2023)
The study critically examines the pivotal role of Tan Malaka in Indonesian political thought and nationalism from 1921 to 1949. Investigating Tan Malaka's background and ideological evolution, the research addresses key questions: What influenced Tan Malaka's political trajectory during 1921-1949, and how did he conceptualize Indonesian nationalism? Employing historical methods, the study meticulously traces Tan Malaka's political journey, beginning with his foray into politics in 1921, association with the PKI, founding of PARI in 1927, and the articulation of the one hundred percent independence concept in 1946. Additionally, it explores the establishment of the Murba Party in 1948, which reflected Tan Malaka's unwavering commitment to resisting colonial diplomacy. The study concludes in 1949 with Tan Malaka's demise, influenced by his call for armed resistance and refusal to negotiate. Despite governmental disapproval and rumors surrounding the Murba Republic, Tan Malaka's legacy endured, evoking widespread sympathy. His profound impact on Indonesian political thought and the nationalist movement persists as a testament to his unwavering dedication to the cause of independence.